VSIG4+ tumor-associated macrophages mediate neutrophil infiltration and impair antigen-specific immunity in aggressive cancers through epigenetic regulation of SPP1 - Zongfu Pan; Jinming Chen; Tong Xu; Anqi Cai; Bing Han; Ying Li; Ziwen Fang; Dingyi Yu; Shanshan Wang; Junyu Zhou; Yingying Gong; Yulu Che; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract V-set and immunoglobulin domain-containing 4 (VSIG4) positive tumor-associated macrophage (VSIG4+ TAM) is an immunosuppressive subpopulation newly identified in aggressive cancers. However, the mechanism how VSIG4+ TAMs mediate immune evasion in aggressive cancers have not been fully elucidated. In our study, we found targeting VSIG4+ TAMs by VSIG4 deficiency or blockade remarkably limited tumor growth and metastasis, especially those derived from anaplastic thyroid cancer (ATC) and pancreatic cancer, two extremely aggressive types. Moreover, the combination of VSIG4 blockade with a BRAF inhibitor synergistically enhanced anti-tumor activity in ATC-tumor bearing mice. VSIG4 deficiency recovered the antigen presentation (B2m, H2-k1, H2-d1) of TAMs and activated antigen-specific CD8+ T cells by promoting their in vivo proliferation and intratumoral infiltration. Notably, loss of VSIG4 in TAMs significantly reduced the production of lactate and histone H3 lysine 18 lactylation, resulting the decreased transcription of SPP1 mediated by STAT3, which collectively disrupted the cell-cell interactions between TAMs and neutrophils. Further combination of VSIG4 with SPP1 blockade synergistically boosted anti-tumor activity. Overall, our studies demonstrate the epigenetic regulation function of VSIG4 confers on TAMs an alternative pattern, beyond the checkpoint role of VSIG4, to shape the immunosuppressive tumor microenvironment and impair antigen-specific immunity against aggressive cancers. Graphical abstract